Swedish media supply 2012 - Asp, Kent (University of Gothenburg, 2018)
The study "Swedish TV supply" is conducted annually since 1998. Since 2012, except for the TV channels SVT1, SVT2, Barnkanalen (the Children Channel), SVT24, Kunskapskanalen (the Knowledge Channel), TV3, TV4, Kanal 5, TV6, Sjuan (Seven), TV8 and the UR program of SVT1 and SVT2, programme of the Swedish Radio (P1, P2, P3, P4 Göteborg, P4 Kristianstad) as well as the play services of some TV channels (SVT play, TV4 play, TV3 play and Kanal 5 play) have been examined. The new name of the study is therefore "Swedish media supply".

The examination of the programs offered on TV is designed to answer five questions: (1) What is the range of supply in the television channels during the program year 2012? (2) What similarities and differences between the television channels' program profiles? (3) What are the programs offered for specific groups: children, youth, minorities and the disabled? (4) How has variety of programmes developed over time? (5) And how is diversity manifested in Swedish television?

The study is based in principle on the information about TV programme from television channels. The programs are classified using this information and starting from a predefined coding scheme.

The radio supply has been coded based on the same principles as the TV supply, even if the classification of the programmes has been adapted to the radio.

The aim of the examination of play services (SVT play, TV4 play, TV3 play and Kanal 5 play) is primarily to compare the supply of the TV channel and its respective play service during the same sample week.

Purpose:

Create repeated, systematic and long-term scientific studies of the programs offered in Swedish television.

Undersökningen "Svenskt tv-utbud" sker årligen sedan 1998. Från och med 2012 undersöktes - förutom tv-kanalernas programutbud (SVT1, SVT2, Barnkanalen, SVT24, Kunskapskanalen, TV3, TV4, Kanal 5, TV6, Sjuan, TV8 samt UR:s program i SVT1 och SVT2) - även programutbudet i Sveriges Radio (P1, P2, P3, P4 Göteborg, P4 Kristianstad) samt tv-kanalernas play-tjänster (SVT play, TV4 play, TV3 play och Kanal 5 play). Det nya namnet på undersökningen är därför "Svenskt medieutbud".

Undersökningen av tv-utbudet avser att besvara fem olika frågor: (1) Hur ser utbudet ut i de enskilda tv-kanalerna under programåret 2012? (2) Vilka likheter och skillnader finns mellan tv- kanalernas programprofiler? (3) Hur ser programutbudet ut till särskilda grupper: barn, ungdomar, minoritetsgrupper och funktionshindrade? (4) Hur har programutbudet utvecklats över tid? (5) Och hur ser mångfalden ut i svensk television?

Undersökningen utgår i princip enbart från kanalernas egen programinformation. Det är med hjälp av denna information som programmen klassificeras med utgångspunkt ifrån ett i förväg bestämt kodningsschema.

Utbudet i radion har kodats efter samma grundprinciper som tv-utbudet, även om klassificeringen av programmen självfallet har anpassats till radion.

Syftet med undersökningen av tv-kanalernas play-tjänster (SVT play, TV4 play, TV3 play och Kanal 5 play) är i första hand att jämföra utbudet med det utbud som respektive tv-kanal sänder under samma urvalsvecka.

Syfte:

Skapa återkommande, systematiska och långsiktiga vetenskapliga studier av programutbudet i svensk television.
Svenskt medieutbud 2012
Keywords: television channels; tv-kanaler; television programmes; tv-program; radio programmes; radioprogram; MEDIA, COMMUNICATION AND LANGUAGE; MEDIA, KOMMUNIKATION OCH SPRÅK; Media; Media; Social Sciences; Samhällsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap